2005
DOI: 10.1523/jneurosci.1147-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetics Change the Excitation/Inhibition Balance That Governs Sensory Processing in the Cat Superior Colliculus

Abstract: The superior colliculus (SC) is a midbrain structure that plays a central role in the integration of information from different sensory modalities and the generation of orienting responses. Its normal function is thought to be governed by a strictly held balance between excitation and inhibition. This hypothesis was tested by recording from the same single units in the SC of cats before the injection of anesthetics, while anesthetics took effect, and after the injections during recovery. Sodium pentobarbital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 60 publications
1
50
0
Order By: Relevance
“…Although the impact of ketamine anesthesia on multisensory processes has been a subject of debate (Populin et al 2002(Populin et al , 2005Stanford et al 2005Stanford et al , 2007, we have seen little difference in the receptive fields or multisensory integrative capacity of neurons in a comparison between the ketamine-anesthetized and awake preparations (Wallace et al 1994(Wallace et al , 1998. The animal was then comfortably supported in the recumbent position without any wounds or pressure points via the head-holding system.…”
Section: Implantation and Recording Proceduresmentioning
confidence: 93%
See 1 more Smart Citation
“…Although the impact of ketamine anesthesia on multisensory processes has been a subject of debate (Populin et al 2002(Populin et al , 2005Stanford et al 2005Stanford et al , 2007, we have seen little difference in the receptive fields or multisensory integrative capacity of neurons in a comparison between the ketamine-anesthetized and awake preparations (Wallace et al 1994(Wallace et al , 1998. The animal was then comfortably supported in the recumbent position without any wounds or pressure points via the head-holding system.…”
Section: Implantation and Recording Proceduresmentioning
confidence: 93%
“…The model assumes independence between the visual and auditory inputs and uses additive factors logic to distinguish between subadditive (contrast Ͻ0), additive (contrast ϭ 0), and superadditive (contrast Ͼ0) modes of response (Perrault Jr et al 2003, 2005Stanford et al 2005Stanford et al , 2007. Significant differences from a contrast value of zero were determined by means of a t-test.…”
Section: Multisensory Interactive Analysesmentioning
confidence: 99%
“…It is unlikely that this is attributable (1) to a specificity of visuo-somatosensory integration because the sign of integration is independent of the particular modalities in play (Meredith and Stein, 1986a;Meredith et al, 1987); (2) to spatial alignment factors: the spatial congruence of bimodal stimuli controls the presence or absence of multisensory integration but not its sign; or (3) to the use of ineffective stimuli (Meredith and Stein, 1986a): the relative proportion of enhancement and depression when both visual and tactile stimuli are effective is very similar to that when only one modality activates the neurons. Some studies have reported higher rates of depression in awake than in anesthetized animals (Populin and Yin, 2002;Bell et al, 2003), suggesting that anesthesia depresses the neuronal activity of inhibitory interneurons (Populin, 2005) or that active fixation, arousal, and selective attention alters the ratio of cortical and subcortical inhibition and excitation (Bell et al, 2003). The parietal cortex is known to play an important role in attentional selection and perceptual decision.…”
Section: Discharge Rate Depression and Enhancementmentioning
confidence: 99%
“…For example, in the avian brain, the selective responses for the BOS observed during periods of synchronized EEG (anesthesia or slow-wave sleep) were not observed in awake birds (Schmidt and Konishi, 1998;Schmidt, 2003, 2004). Similarly, the strength of evoked responses and the temporal discharge patterns in the mammalian auditory system differ considerably between anesthetized and awake animals (Torterolo et al, 2002;CotillonWilliams andEdeline, 2003, 2004;Massaux et al, 2004;Populin, 2005); for other references see (Hennevin et al, 2007). Thus, in the present study, to ensure that the anesthetic did not mask some aspect of the neural code that is in use in awake animals, we also analyzed neuronal spike trains recorded in the auditory cortex of awake guinea pigs.…”
Section: Introductionmentioning
confidence: 99%